1977
DOI: 10.1177/002221947701000708
|View full text |Cite
|
Sign up to set email alerts
|

Recategorized WISC-R Scores of Learning Disabled Children

Abstract: This study assesses the utility o f Bannatyne's recategorization o f subtest scaled scores on the WISC-R (Wechsler 1974). The WISC-R was administered to 208 school-verified learning disabled (L D) children. The obtained subtest scaled scores were recategorized in the manner suggested by Bannatyne (1974) into Spatiol, Conceptual, Sequential, and Acquired Knowledge categories. The mean Spatial score was significantly greater than the mean Conceptual score, which, in turn, exceeded the Sequential and Acquired Kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

1980
1980
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(23 citation statements)
references
References 7 publications
2
20
1
Order By: Relevance
“…In addition, the present results are consistent with previous studies which found that learning disabled students tend to have lower FD factor scores than do adequate achievers (Rugel, 1974;Smith, Coleman, Dokecki, & Davis, 1977), and that the FD factor may tap attentional elements (Bush & Waugh, 1976). However, caution is recommended when interpreting the significant relationship between Arithmetic WRAT scores and the FD factor as due to attentional deficiencies because of potential overlap between predictor and criterion variables (i.e., WISC-R Arithmetic and WRAT Arithmetic subtests).…”
Section: Resultssupporting
confidence: 92%
“…In addition, the present results are consistent with previous studies which found that learning disabled students tend to have lower FD factor scores than do adequate achievers (Rugel, 1974;Smith, Coleman, Dokecki, & Davis, 1977), and that the FD factor may tap attentional elements (Bush & Waugh, 1976). However, caution is recommended when interpreting the significant relationship between Arithmetic WRAT scores and the FD factor as due to attentional deficiencies because of potential overlap between predictor and criterion variables (i.e., WISC-R Arithmetic and WRAT Arithmetic subtests).…”
Section: Resultssupporting
confidence: 92%
“…Relative but not absolute superiority on the WISC-R Performance Scale was also reported by Smith, Coleman, Dokecki, and Davis (1977) for children classified simply as ''learning disabled.'' While we cannot know what type of learning disabilities these children actually had, it is likely that many were dyslexic since dyslexia is the most prevalent form of diagnosed learning disability (Springer & Deutch, 1997).…”
mentioning
confidence: 92%
“…Several studies have found the Spat i a l Conceptual > Sequential pattern on a group-wide basis with the recategorized WISC-R scores of LD children (Gutkin 1979, Smith, Coleman, Dokecki, & Davis 1977, Vance & Singer 1979.) The utility of the recategorization hierarchy for identifying LD children on an individual basis has not yet been demonstrated, however.…”
mentioning
confidence: 99%